2018
DOI: 10.1507/endocrj.ej17-0543
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits glucose oxidation and insulin secretion in rat islets

Abstract: Abstract. Glucose promotes insulin secretion primarily via its metabolism and the production of metabolic coupling factors in beta-cells. The activation of AMP-activated protein kinase (AMPK), an energy sensor, results in a decrease in insulin secretion from beta-cells, but its mechanism remains largely unknown. Berberine, an oral anti-diabetic drug, has been shown to activate AMPK in multiple peripheral tissues. Here, we examined the effects of berberine and AMPK activation on insulin secretion and glucose ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…1). This effect was found in pancreatic islets of rat, mouse and also human [3, 13, 40, 73]. In spite of some species differences related to β cell biology [41, 63, 69], the results regarding AMPK indicate that the influence of glucose is similar in rodent and human islets.…”
Section: The Link Between Ampk and Insulin Secretionmentioning
confidence: 97%
See 1 more Smart Citation
“…1). This effect was found in pancreatic islets of rat, mouse and also human [3, 13, 40, 73]. In spite of some species differences related to β cell biology [41, 63, 69], the results regarding AMPK indicate that the influence of glucose is similar in rodent and human islets.…”
Section: The Link Between Ampk and Insulin Secretionmentioning
confidence: 97%
“…Insulin secretion is a dynamic process and changes rapidly in response to various regulatory agents. In this context, the phosphorylation level of AMPKα (Thr172) was shown to be reduced already after short-term (30–60 min) exposure of pancreatic islets to glucose [3, 32, 73]. However, in the case of more prolonged (16–20 h) incubations of islets with increased concentrations of glucose, pAMPK is also reduced [13, 32].…”
Section: The Link Between Ampk and Insulin Secretionmentioning
confidence: 99%
“…7C). It was previously demonstrated that insulin secretion was reduced from rat islets pretreated with media containing BBR (Bai et al, 2018). Reductions in insulin secretion under low glucose conditions were detected when palmitate was added to the media (Zhou et al, 2008).…”
Section: Dietary Bbr Supplementation Preserved Pancreatic β-Cell Funcmentioning
confidence: 98%
“…Research on the mechanism of action in this area is relatively scarce. One possible mechanism is BBR inhibited GSIS via the KATP-dependent triggering pathway [ 56 ].…”
Section: Studies On the Bbr Mechanismmentioning
confidence: 99%